2004
DOI: 10.1007/s00213-003-1576-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effects of receptor-selective ligands in rats discriminating the novel antipsychotic quetiapine

Abstract: Together with data from a previous study (Smith and Goudie 2002) in which we observed full generalization to quetiapine with olanzapine, risperidone and clozapine, but not with typical antipsychotics (such as haloperidol) or the novel antipsychotic amisulpride, these data suggest that: i) the discriminative stimulus properties of quetiapine, like those of clozapine, probably reflect a "compound" stimulus which involves several classes of receptor; ii) the quetiapine cue is of value in analysing, and screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Because most selective receptor ligands (the exception being muscarinic receptor antagonists) do not reliably substitute for CLZ while drugs with a more diverse binding profile do, it has been suggested that CLZ has a compound DS Porter et al 2000b). Somewhat similar results have been reported for the atypical APD quetiapine, which seems to have drug discrimination properties similar to CLZ (Smith and Goudie 2002;Goudie et al 2004). Goudie et al (2004) concluded that muscarinic antagonism is sufficient, but not necessary, to produce full substitution to quetiapine as risperidone (which has minimal muscarinic activity) fully substitutes for quetiapine (Smith and Goudie 2002).…”
Section: Introductionmentioning
confidence: 68%
“…Because most selective receptor ligands (the exception being muscarinic receptor antagonists) do not reliably substitute for CLZ while drugs with a more diverse binding profile do, it has been suggested that CLZ has a compound DS Porter et al 2000b). Somewhat similar results have been reported for the atypical APD quetiapine, which seems to have drug discrimination properties similar to CLZ (Smith and Goudie 2002;Goudie et al 2004). Goudie et al (2004) concluded that muscarinic antagonism is sufficient, but not necessary, to produce full substitution to quetiapine as risperidone (which has minimal muscarinic activity) fully substitutes for quetiapine (Smith and Goudie 2002).…”
Section: Introductionmentioning
confidence: 68%
“…Nonetheless, it remains possible that mirtazapine elicits a "compound" DS-that is, composed of multiple stimulus elements-by analogy to atypical agents like the antipsychotics, clozapine and quetiapine, that interact with an array of targets (Hoenicke et al 1992;Kelley and Porter 1997;Goudie et al 2004;Prus et al 2006;Cole et al 2007). Accordingly, as previously proposed for antipsychotics, further insights into the DS actions of mirtazapine may be acquired in substitution studies with mirtazapine to selective ligands acting at sites potentially implicated in its interoceptive profile (Prus et al 2006;Goudie et al 2004;Cole et al 2007). Furthermore, as for other classes of ligand that interact with multiple receptors and display complex mechanisms of action, it is conceivable that other (higher or lower) doses of mirtazapine may yield differing patterns of substitution (see above citations).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to drug discrimination assays with psychoactive agents like antipsychotics (see this Special Issue; Dekeyne and Millan 2003;Goudie et al 2004;Alici et al 2006), antidepressant discrimination studies remain comparatively uncommon. This is unfortunate since discriminative stimulus (DS) studies are potentially instructive in evaluating several interesting issues: first, in determining whether a training drug shares interoceptive effects with other classes of clinically active antidepressant; second, in characterizing mechanisms of action involved in the interoceptive effects of antidepressants using substitution tests with ligands selective for specific classes of receptor and transporter; third, in relating DS properties of antidepressants to their functional actions, including their influence upon mood.…”
Section: Introductionmentioning
confidence: 99%
“…quetiapine, the atypical antipsychotic drug zotepine produced a maximum of 54% quetiapine-appropriate responding (Goudie et al 2004a). Finally, Goudie et al (2004b) examined the underlying receptor mechanisms involved in the discriminative stimulus properties of quetiapine [rats trained to discriminate quetiapine 10.0 mg/kg (i.p.) from vehicle].…”
Section: Quetiapinementioning
confidence: 99%
“…Muscarinic receptor antagonism appears to be important for the discriminative stimulus properties of olanzapine (Porter et al 2000a), quetiapine (Goudie et al 2004b), and chlorpromazine . However, olanzapine's cue clearly involves serotonergic receptors as well since ritanserin has been shown to fully substitute for olanzapine (Porter et al 2000a).…”
Section: Discriminative Stimulus Properties Of the Typical Antipsychomentioning
confidence: 99%